Saturday

July 26, 2014

July 26, 2014

Posted by **Jordyn** on Thursday, September 24, 2009 at 6:16pm.

- Math -
**Marie**, Thursday, September 24, 2009 at 6:36pm18x-(8x-7)=67

18x-8x+7=67

10x+7=67

10x=60

x=6

**Related Questions**

math - when I have (2x^(3)-18x)-(2x^(3)) / (x^(2)-9) am I suppose to be left ...

Algebra - checking problem Use FOIL to multiply: (6x – 1)(3x – 4) 6x*3x + 6x*(-4...

Math - Find the Least Common multiple of the two expressions: 24x^2-96 & 18x^2+...

Math - How can we factor trinomial: 36x^2+18x+0 Is thislike this: 18x(2x+1)

Math - 9x^2+16y^2-18x+64y-71=0 find the coordinates of the center, the foci, and...

college algebra - y intercept: 3x^2+18x 0=3x^2+18x from here im lost

Math - i'm a bit stuck with this.. 145/18 = x + x^2 what does x equal to? ...

Pre-Cal - Classify the conic and write the equation in standard form: (1) 9x^2...

math - help my daughter has a math problem and came to me for help, I am lost...

math! - determine two geometreic sequences whose first terms are 18x-9, 2x+8 and...